Metabolism and immune memory in invertebrates: are they dissociated? - Méndez-López, Texca T.; Carrero, Julio César; Lanz-Mendoza, Humberto; Ochoa-Zarzosa, Alejandra; Mukherjee, Krishnendu; Contreras-Garduño, Jorge (Frontiers in Immunology, 2024)
Since the discovery of specific immune memory in invertebrates, researchers have y investigated its immune response to diverse microbial and environmental stimuli.Nevertheless, the extent of the immune system's interaction with metabolism, remains relatively enigmatic. In this mini review, we propose a comprehensive investigation into the intricate interplay between metabolism and specific immune memory. Our hypothesis is that cellular endocycles and epigenetic modifications play pivotal roles in shaping this relationship. Furthermore, we underscore the importance of the crosstalk between metabolism and specific immune memory for understanding the evolutionary costs. By evaluating these costs, we can gain deeper insights into the adaptive strategies employed by invertebrates in response to pathogenic challenges. Lastly, we outline future research directions aimed at unraveling the crosstalk between metabolism and specific immune memory. These avenues of inquiry promise to illuminate fundamental principles governing host-pathogen interactions and evolutionary trade-offs, thus advancing our understanding of invertebrate immunology.